Fundamental movement skills and physical activity of children in low-income families - Karisman, Vicki Ahmad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The purpose of the study was to determine the level of physical activity and basic movement skills in low-income families. The method used in this study is a quantitative descriptive method through surveys. The study sample included 32 children aged ± 9 years, consisting of 19 boys and 13 girls from low-income families. Sampling techniques use purposive sampling. The instruments used in the study were the population income category, the 2nd Edition Test of Gross Motor Development (TGMD), and the Instrument Physical Activities Questionnaire (IPAQ). The results showed that children in low-income families tend to have a body mass index underweight (thin), and basic movement skills are lacking. But in physical activity, boys tend to be moderate, and children tend to be low (low). This study is expected to be data on physical activity and basic movement skills in children from low-income families to be followed up through various activity programs in schools.